Conflict at higher education institutions: factors and solutions for Yemen. Issue 2 (4th March 2018) - Muthanna, Abdulghani; Sang, Guoyuan
Abstract: This is a qualitative case study focusing on reporting the dynamics that cause conflicts between academics and administrators in higher education in Yemen. Drawing upon a critical review of two policy documents, observational research and in-depth interviews with 59 administrators and academics, the article presents the key factors for conflict in higher education and provides a model for resolving it.